Adidas x Parley : an exploration of corporate social responsibility and the global plastic crisis - Murfree, Jessica; Police, Chelsea (London : Human Kinetics, Inc., 2022)
Stemming from the 2015 partnership between Adidas and Parley, this case examines sport organizations' relationship to the natural environment and the incorporation of corporate social responsibility initiatives through strategic partnerships. Adidas and Parley joined forces to design and produce sustainable athletic apparel using recycled ocean plastic. While Parley's founding goal is to reduce ocean plastic pollution, students should rely upon environmental issues, the plastic crisis, sport's relationship with the natural environment, and Carroll's CSR pyramid to assess and improve Adidas' strategies to fight these mounting issues. Since the partnership's conception, Adidas has exceeded its original sustainability goals and continues to incorporate environmental protection into its overall business model. Perhaps organizations like Parley alongside Adidas can serve as a catalyst for other sport organizations to do the same. Adidas and Parley's relationship has further highlighted the need for sport organizations to become more environmentally conscious, given the sport industry's impact on the natural environment and vice versa. This case challenges students to step into the role of Adidas' Assistant Director of Global Partnerships and think critically about environmental sustainability for sport organizations and provide further suggestions for promoting and implementing proenvironmental business practices within an organization.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Plastics -- Environmental aspects -- Case studies